(untitled) (Scientific journal of the Fergana State University, 2026)
The article highlights the poetic skill of the Uzbek poet Oybek through the study of the meter characteristics of his poems. Oybek played an important role in the development of poetic thought in Uzbek lyrics of the 20th century, and the study of the characteristics of his poetry is relevant in that it is important in determining the stages of development of the lyrics of the subsequent period. The article was studied using such research methods as structural-poetic, historical-comparative, historical-cultural, classification, psychological, hermeneutic, and descriptive. It was revealed that Oybek, who conducted continuous creative research on the improvement of the form of poetry, also achieved great success in revealing the wide possibilities of meter, stanza, and rhyme in various contexts. The formal features of the poet’s poetry serve the ideological impact and content, the attractiveness of the image and figurative expression. It is studied how Oybek expresses his admiration for the beauty, complexity and complexity of man and nature in various rhythms ranging from five to fifteen syllables.